Factors associated with the hospitalization of COVID-19 patients in a clinic’s intensive care unit in 2020 - Lozano, Ysabel (2021)
Objective: To identify the factors associated with the hospitalization of COVID-19 patients in an intensive care unit. Materials and methods: An observational, cross-sectional and analytical study. The sample consisted of COVID-19 patients treated at the Clínica Good Hope from April to June 2020. The variables were: outcome (place of hospitalization: intensive care unit or internal medicine service) and exposure (age, sex, disease period, comorbidities and laboratory tests such as levels of lactate dehydrogenase, ferritin, D-dimer and C-reactive protein). A descriptive, bivariate analysis and a simple GLM Poisson regression were performed to calculate the odds ratio (OR). Results: Seventy-six (76) patients were evaluated (60 in the internal medicine service and 16 in the intensive care unit). The mean age was 52 years and males prevailed (81.6 %). Elevated serum levels of lactate dehydrogenase, D-dimer and C-reactive protein were associated with a 0.02 % more chance of admission to the intensive care unit at the time of hospitalization, which is statistically significant (OR: 1.002, 95 % CI: 1.001 - 1.003; OR: 1.05, 95 % CI: 1.01 - 1.10; and OR: 1.06, 95 % CI: 1.02 - 1.09). Conclusions: The levels of lactate dehydrogenase, D-dimer and C-reactive protein are associated with the admission to an intensive care unit during hospitalization and could reflect the severity of the disease.